2007
DOI: 10.1097/01.rhu.0000260497.84746.dd
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Mandatory Rheumatology Osteoporosis Consultation in Patients With Low-Impact Hip Fracture

Abstract: In our institution, we were successful in identifying and initiating appropriate therapy for osteoporosis patients through an automatic rheumatology osteoporosis consultation after hip fracture. The implementation of a mandatory osteoporosis consult resulted in a statistically significant increase in treatment of the exposed group compared with the unexposed group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…For example, in Hawker et al [2] and Laslett et al [11], combinations of OP medications and supplements were reported such that we could not discriminate between medication and supplements. Similarly, Quintos-Macasa [32] reported "treatment" as calcium, vitamin D, or OP medication and Gardner et al [6] reported "treatment" as including calcium and OP medication together.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Hawker et al [2] and Laslett et al [11], combinations of OP medications and supplements were reported such that we could not discriminate between medication and supplements. Similarly, Quintos-Macasa [32] reported "treatment" as calcium, vitamin D, or OP medication and Gardner et al [6] reported "treatment" as including calcium and OP medication together.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although a number of postfracture interventions have been attempted (Table 5), the most successful were those performed in the hospital. [7][8][9][10] The most comprehensive of these was the Kaiser Southern California program, which included a standardized admission order sheet with screening for secondary causes of osteoporosis and discharge orders with referral for fall prevention, a primary care or specialty consult for evaluation of secondary causes of osteoporosis, and options for the surgeon to order a DXA scan and antiosteoporosis medications. 11 Successful improvements in therapy were also achieved in the outpatient setting when patients were recruited by medical records review during hospitalization or after discharge 12 or identified through orthopaedic billing records 13 and requested to be enrolled in an osteoporosis management program.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies were educational interventions directed to the primary care provider either directly from the orthopaedic surgeon [35][36][37][38][39] or indirectly via the patient [25,[40][41][42][43]. One intervention focused on providing patient-specific education including BMD results directly to the primary care physician [22].…”
Section: Review Of Case-finding Systems In Fracture Unitsmentioning
confidence: 99%